Smartphone use for language receptive skills: A guided approach / Nur Ain Abdul Malek, Nor Syamimi Iliani Che Hassan and Nor Hairunnisa Mohammad Nor - Abdul Malek, Nur Ain; Che Hassan, Nor Syamimi Iliani; Mohammad Nor, Nor Hairunnisa (Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
It is not uncommon to find smartphones being used in classrooms throughout the world. However, despite the prevalent usage, the extent to which this technological gizmo has contributed to academic achievement particularly language performance is still inconclusive. The study seeks to contribute to the debate with the objectives of identifying the correlation between guided smartphone use and students’ English language performance and determining the impact of guided smartphone use on students’ receptive language skills. The study adopted a quantitative method and employed an experimental research design. Pre and post reading and listening tests were administered and tabulated according to categories. To measure reading and listening competence, the scores collected from the pre- and post-test were computed using SPSS to compare inter- and intra-group differences. The inter-group comparisons were analysed by Independent Samples Test and the intra-group comparisons by Paired Samples Statistics. The findings of this research revealed that guided approach of smartphone use did not give significant impact on students’ language performance. However, intra-group analysis found there were significant positive changes in post-test scores for reading skill although not for listening skill post-test scores.